What attracts human capital?: understanding the skill composition of interregional job matches in Germany - Arntz, Melanie (Regional studies, 2010)
Arntz M. What attracts human capital? Understanding the skill composition of interregional job matches in Germany, Regional Studies. By examining pecuniary and non-pecuniary factors in the destination choices of heterogeneous job movers, this paper tries to explain the skill composition of interregional job matches in Germany. It thus provides insights on how policy can affect the spatial allocation of human capital to promote convergence between regions such as eastern and western Germany. Estimates from a nested logit model suggest that the spatial pattern of job moves by high-skilled individuals are mainly driven by interregional income differentials, while interregional job matches by less-skilled individuals are mainly determined by interregional differentials in job opportunities. The role of regional amenities in attracting high-skilled labour turns out to be less clear.
Zusammenfassung in englischer, chinesischer, französischer, deutscher und spanischer Sprache